Development of an End-of-Life Nursing Care Protocol for Intensive Care Units: Delphi Survey Method. Issue 4 (27th August 2022) - Kim, Jungeun; Yun, Hye Young; Kim, Euni Ji; Kim, Hyunsook; Kim, Geon Ah; Kim, Sung Ha; Koo, Jayoung; Park, Ju Youn; Park, Aisoon; Han, Eugene; Kim, So Yeon; Jeong, Jihye; et al.
Abstract : Because of the lack of guidelines and standardized protocols for end-of-life nursing care in intensive care units in Korea, many nurses have reported facing difficulties when providing care for patients. This study attempted to develop a standardized end-of-life nursing protocol for use in intensive care units. A draft of the end-of-life nursing care protocol was developed after a literature review. A Delphi survey was carried out twice with 30 experts, and the content validity ratio of the items was investigated. The draft end-of-life nursing care protocol was divided into 3 separate stages with 24 items: 8 initial end-of-life care assessment items, 5 ongoing end-of-life care items, and 11 post–end-of-life care items. The content validity ratios of the first and second rounds were 0.33 or greater in each category, demonstrating the validity of the proposed draft as a standardized protocol. Furthermore, at the suggestion of the experts, an extra item was added in the last stage, resulting in 25 items. The results of this study are expected to help leading hospitals in South Korea outline the roles and range of tasks for end-of-life care in an intensive care unit and thereby resolve difficulties for nurses. Furthermore, this will improve the medical services that family members receive during end-of-life care.